Monetary Policy under the Microscope: Intra-bank Transmission of Asset Purchase Programs of the ECB - Lisa Cycon; Michael Koetter (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2015)
With a unique loan portfolio maintained by a top-20 universal bank in Germany, this study tests whether unconventional monetary policy by the European Central Bank (ECB) reduced corporate borrowing costs. We decompose corporate lending rates into refinancing costs, as determined by money markets, and markups that the bank is able to charge its customers in regional markets. This decomposition reveals how banks transmit monetary policy within their organizations. To identify policy effects on loan rate components, we exploit the co-existence of eurozone-wide security purchase programs and regional fiscal policies at the district level. ECB purchase programs reduced refinancing costs significantly, even in an economy not specifically targeted for sovereign debt stress relief, but not loan rates themselves. However, asset purchases mitigated those loan price hikes due to additional credit demand stimulated by regional tax policy and enabled the bank to realize larger economic margins.
urn:nbn:de:gbv:3:2-48588
Keywords: G01; G21; E42; E43; E52; 330; unconventional monetary policy; asset purchase programs; ECB; interest rate channel; internal capital markets